Предмет: Алгебра,
автор: Ddgvss
Решите уравнение (x+1)^3=x^2 (x+1)
Ответы
Автор ответа:
0
(х+1)^3-х^2*(х+1)=0
(х+1)*((х+1)^2-х^2)=0
х+1=0
(х+1)^2-х^2=0
х=-1
х=-1/2
(х+1)*((х+1)^2-х^2)=0
х+1=0
(х+1)^2-х^2=0
х=-1
х=-1/2
Автор ответа:
0
Решение:
( х + 1) ³ = х²·( х +1 )
( х + 1) ³ - х²·( х +1 ) = 0
( х + 1) · ( ( х +1 )² - х²) = 0
( х + 1) · ( х² +1² + 2х - х²) = 0
( х + 1) · (1 + 2х ) = 0
х + 1= 0 или 1 + 2х = 0
х + 1 = 0 2х = -1
х = -1 х = -0,5
Ответ: -1 ; - 0,5.
( х + 1) ³ = х²·( х +1 )
( х + 1) ³ - х²·( х +1 ) = 0
( х + 1) · ( ( х +1 )² - х²) = 0
( х + 1) · ( х² +1² + 2х - х²) = 0
( х + 1) · (1 + 2х ) = 0
х + 1= 0 или 1 + 2х = 0
х + 1 = 0 2х = -1
х = -1 х = -0,5
Ответ: -1 ; - 0,5.
Похожие вопросы
Предмет: Қазақ тiлi,
автор: aizadaenshalieva
Предмет: Алгебра,
автор: ilona2907
Предмет: Геометрия,
автор: leramolodina25
Предмет: Литература,
автор: alekseymars
Предмет: Биология,
автор: Wemms